A Review of the Epidemiology of Lassa Fever in Nigeria - Danny Asogun; Bosede Arogundade; Faith Unuabonah; Olorunkemi Olugbenro; Joyce Asogun; Fatelyn Aluede; Deborah Ehichioya (Microorganisms, 2025)
Lassa fever, a viral hemorrhagic illness that first came into the limelight as a clinical entity in 1969 when it was discovered in Northern Nigeria, is now found in other West African countries such as Sierra Leone, Liberia, Guinea, Togo, and the Benin Republic. Over the years, the disease, which is primarily transmitted from contact with infected mastomys rodents to humans, has the capability of secondary human-to-human transmission with significant morbidity and mortality, especially in healthcare settings. The disease is typically characterized by seasonal outbreaks, which peak during the dry season months of December to March. Lassa fever significantly impacts public health and the socioeconomic life of people in affected communities. In Nigeria, the Integrated Disease Surveillance and Response Strategy (IDSR), along with other medical countermeasures, have been employed to curtail the impact of the disease in endemic regions of Nigeria and other West Africa countries. The one-health approach to combat the disease is a promising strategy. This, along with the hope of a safe and effective vaccine, is a ray of hope on the horizon for public health authorities in Nigeria and other West African countries that the battle against Lassa fever might indeed end sooner than later.